Organoids and microphysiological systems: Promising models for accelerating AAV gene therapy studies - Ramamurthy, Ritu Mahesh; Atala, Anthony; Porada, Christopher D.; Almeida-Porada, Graҫa (Frontiers in Immunology, 2022)
The FDA has predicted that at least 10-20 gene therapy products will be approved by 2025. The surge in the development of such therapies can be attributed to the advent of safe and effective gene delivery vectors such as adeno-associated virus (AAV). The enormous potential of AAV has been demonstrated by its use in over 100 clinical trials and the FDA’s approval of two AAV-based gene therapy products. Despite its demonstrated success in some clinical settings, AAV-based gene therapy is still plagued by issues related to host immunity, and recent studies have suggested that AAV vectors may actually integrate into the host cell genome, raising concerns over the potential for genotoxicity. To better understand these issues and develop means to overcome them, preclinical model systems that accurately recapitulate human physiology are needed. The objective of this review is to provide a brief overview of AAV gene therapy and its current hurdles, to discuss how 3D organoids, microphysiological systems, and body-on-a-chip platforms could serve as powerful models that could be adopted in the preclinical stage, and to provide some examples of the successful application of these models to answer critical questions regarding AAV biology and toxicity that could not have been answered using current animal models. Finally, technical considerations while adopting these models to study AAV gene therapy are also discussed.